2014
DOI: 10.1007/s12272-014-0489-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized nanoparticles based on chitosan-folic acid and dextran succinate-doxorubicin conjugates for drug targeting

Abstract: Folic acid-decorated self-organized nanoparticles were fabricated to target folate receptor of cancer cells. Doxorubicin (DOX) was conjugated with carboxyl group of dextran backbone using succinic anhydride (DexSU-DOX). DOX-loaded self-organized nanoparticles were prepared by complexation with folic acid-grafted chitosan (ChitoFA) and DexSU-DOX. Nanoparticles in the aqueous environment have spherical shapes with average size less than 100 nm and their sizes were increased by coated with ChitoPEG or ChitoFA. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Due to abnormal leaky (new or neo) vasculature and impaired lymphatic drainage, small non targeted particles (<400 nm) circulating in the blood tend to accumulate in the interstitial space of tumors and inflamed tis- [121][122][123][124][125][126][127][128][129][130] sues, a known hallmark of cancer (Fig. 2) [3].…”
Section: Passive Targetingmentioning
confidence: 99%
“…Due to abnormal leaky (new or neo) vasculature and impaired lymphatic drainage, small non targeted particles (<400 nm) circulating in the blood tend to accumulate in the interstitial space of tumors and inflamed tis- [121][122][123][124][125][126][127][128][129][130] sues, a known hallmark of cancer (Fig. 2) [3].…”
Section: Passive Targetingmentioning
confidence: 99%
“…The results revealed that folic acid-dextran (FADex) nanoparticles effectively suppressed tumour growth by folate receptor targeting. These results suggested that DOX-loaded FADex nanoparticles are potential carriers for anticancer drug delivery 46 . The folate-grafted chitosan nanoparticles showed greater efficiency in cell uptake, approximately twice that of the non-folate grafted chitosan nanoparticles.…”
Section: Doxorubicinmentioning
confidence: 82%
“…However, the cellular uptake of FA-nanogels only reached about 50% of the initial in the presence of 0.5 mM FA and was further suppressed to 20–25% of the initial in the presence of 10 mM FA [50]. Similarly, it was shown that pre-treatment or the presence of free FA (1–2 mM) significantly reduced the cellular uptake or the cytotoxicity potency of FA-conjugated nanomedicines including FA-appended methyl-b-cyclodextrin (FA-M-β-CyD), FA-anchored cucumber mosaic virus (FA-CMV), or FA-decorated self-organized NPs (FADex NPs) [42, 47, 48]. …”
Section: Fa-decorated Nanomedicinesmentioning
confidence: 99%